An Empirical Investigation of the Association Between Company Attributes and Disclosure Score of Indian Companies - Kaur, Narinder; Arora, R. S. (Indian Journal of Finance, 2013)
The main thrust of this paper is to investigate the company attributes and their influence on corporate disclosure. The study examined the level of disclosure on the basis of index of disclosure consisting of 101 items by analyzing the annual reports of 19 public sector and 23 private sector non-financial Indian companies selected on the basis of their market capitalization from BSE-500 index. The study covers a period of eight years from 2003-04 to 2010-11. This study investigates the impact of company attributes i.e. Turnover of the Company, Fixed Assets of the company, ROCE (Profitability of the company), Age of the Company, Board Size, Proportion of Independent Directors on Board, Attendance of Independent Directors in Board Meetings, Listing Status of the Company, Promoters' Holding, Institutional Holding , and Nature of Industry on Disclosure score of public and private sector companies in India by using the multiple regression analysis. The study indicates that Turnover, Proportion of Independent Directors, and Institutional Holding have a positive and significant impact on Disclosure score of public sector companies. In case of the private sector, the study highlights that Turnover, Age, Listing Status, D3 (Minerals and Metals), and D4 (Chemical and Fertilizers) industries have a positive and significant influence on the Disclosure score.